Oil charge and biodegradation history in an exhumed fractured reservoir, Devonian, UK. (March 2019) - Baba, Mas'ud; Parnell, John; Muirhead, David; Bowden, Stephen
Abstract: The distribution of oil residues in fractured Upper Devonian reservoir sandstones of Caithness help us to understand relationships between oil charge and episodes of fracturing. The sandstones are cut by an extensive set of tightly cemented deformation bands in the vicinity of the Brough Fault, and calcite-mineralized open fractures. The deformation bands compartmentalized the reservoir, which subsequently was charged by oil to varying extent in different compartments. Petrographic and biomarker data distinguish two charges of oil. The first charge of oil was unaltered. The later mineralized fractures introduced a heavier biodegraded oil that spread into the sandstone pores and displaced/overprinted the earlier oil. Two distinct oil charges are also evident from two generations of oil fluid inclusions, firstly in overgrowths on quartz grains, and secondly in the calcite veins, exhibiting distinct fluorescence characteristics. Migration and trapping of oil depended on the combination of two fracturing episodes of different character, in which the first episode created sealed compartments which were then filled by oil introduced by the second episode. Highlights: Onshore exposure of oil-charged reservoir. Geochemistry shows two stages of oil charge. Second stage oil charge is more biodegraded. Two stages of fracturing: deformation bands and later mineralized fractures. Study places stages of oil charge and fracturing into sequence of events.